Kemampuan Membaca Memahami Teks Bahasa Jerman - Maoedhy Dwi Joeliea; Hasmawati Hasmawati; Mantasiah R (Phonologie : Journal of Language and Literature, 2021)
Abstract. The purpose of this research was to determine the level of ability to read and understand German texts for students of class XI MIPA 3 of SMA Negeri 1 Tolitoli. This research uses a descriptive method. For data collection, a written test was used. The test consists of multiple choice, matching test and true-false test. Furthermore, the data were analyzed by using the percentage technique. The population in this study were all students of class XI MIPA at SMA Negeri 1 Tolitoli which consisted of 5 classes with 180 students. The sample of this study was the students of class XI MIPA 3 as many as 26 students who were selected using random sampling. The results of this study indicate that the ability to read and understand German texts in class XI MIPA 3 SMA Negeri 1 Tolitoli is in the good category (80.5%).